SUCCESSION MANAGEMENT IN PUBLIC UNIVERSITIES IN GHANA: CONTEXT, PROSPECTS AND SUCCESS FACTORS - A REVIEW OF LITERATURE - Wonnia, L. K. (UDS International Journal of Development, 2022)
Ghana, a sub-Saharan African country has been noted to be among the countries with a high rate of unemployment. An insight into the current trends in succession management in public institutions provides a panoramic view of the context, prospects, and success factors in the implementation of succession management in public universities in Ghana. As a country with a high unemployment rate coupled with a high rate of corruption and poverty, succession management has been found to be a challenging issue for university administrators and other stakeholders in the country. Routine procedures are not followed for replacement of workers who in one way or the other left their jobs. Also, the study found that new workers do not have the required skills and experience due to protocols involved in the recruitment and succession processes. The study, therefore, recommends, among others, the adoption of effective training and the flat management structure to enhance the implementation of succession management in public universities in Ghana. Keywords: Career Opportunities, Recruitment, Succession Management, Talent Management, Ghanaian Universities